Impact of Supply Chain Disruptions on Economic Growth: Insights From a Major Public Health Crisis - Hui Jin; Jiamin Xue; Kuen-Lin Lin; Haochuan Yang; Zhenyu Zhu (SAGE Publishing, 2024)
Supply chain disruptions caused by major public health crises will severely impact the economic growth. The main purpose of this paper is to examine the above proposition, taking the strict lockdown policy and supply chain disruption in Hubei Province at the beginning of the COVID-19 epidemic as a case, to provide decision-making reference for the government in supply chain management under major public health crisis. To achieve this goal, this paper firstly measures the supply chain network of Hubei province via the multi-region and multi-sector value-added model; then empirically studies the impact of lockdown policy and supply chain disruption on provincial economic growth, with the monthly data of 31 provinces covering January 2018 to December 2022, by the Difference in Difference method. The results show that: the lockdown policy and supply chain disruption under the Covid-19 epidemic negatively affected provincial economic growth; moreover, supply chain disruptions make provinces closer to Hubei more vulnerable to economic shocks. The results are significant in the placebo test, and are further supported in the robustness test of alternative variables and data. We further discussed the Business Cycle Co-movement between Hubei and other provinces, and the probable impact mechanism of supply chain interruption on economic growth in the Covid-19 epidemic. This study shows that supply chain network plays an important role in the transmission of interregional economic shocks, as well as its importance for economic growth, especially in major public health crises.